Interprofessional education clinical placement program: a qualitative case study approach. Issue 6 (2nd November 2021) - Naumann, F. L.; Nash, R.; Schumacher, U.; Taylor, J.; Cottrell, N.
ABSTRACT: The goal of health professional education programs is to produce competent graduates, with an ability to work collaboratively as effective healthcare team members. We explored the reflections of students and clinical facilitators, in response to participation in a structured interprofessional education (IPE) clinical placement program. In our qualitative study we used an exploratory case study design. In our analysis, we highlight the benefits of interprofessional practice. Key themes identified by students included: limited opportunities to engage in IPE across their course; lack of clarity around IPE; value of IPE for students, practitioners, and patient outcomes; and need for IPE opportunities to be integrated into placements. Key themes identified by the clinical facilitators included: being reminded of the value of IPE for students and patients; preparation for IPE placements need to be embedded in curricula; coordination and communication of IPE learning activities need to be clear for staff and students; and IPE should continue as part of the broader clinical education agenda. Our findings reinforce the notion that students and clinical facilitators value the importance of IPE for student learning within the clinical placement setting. The outcomes offer valuable insights for universities and hospital and health care contexts for setting up and implementing IPE activities, and we provide recommendations for improving ongoing IPE efforts within clinical placement setting.